(untitled) - Meier, Gerald M. (New York, 1957)
This book examiness the problems of accelerating development in poor countries and maintaining development in rich countries. From the viewpoints of theory, historry, and policy it attempts to explain the forces that give long-period growing power to an economy.
Keywords: Economic development,Phát triển kinh tế